Quality of Service on Road User Satisfaction: Study on Surabaya-Malang Toll Road Customers - Subkhan, Muhammad Fajar; Maruta, IGN. Anom; Mahendra, IGN. Andhika (International Journal of Social and Management Studies, 2023)
Travel satisfaction can be considered as a type of road user satisfaction. This level of satisfaction is possible to arise as a result of the performance of Road User Satisfaction with the Services provided by the toll road infrastructure manager in relation to the response of road users to the road services. So this study aims to analyze the quality of service in terms of the satisfaction of users of the Surabaya-Malang toll road. Quantitative research with a community satisfaction survey approach, taking incidental purposive sampling. The sample size used the Slovin formula with a 5% margin of error, and data was collected using a Thurstone scale model questionnaire and distributed to 388 respondents. The research instrument is composed of 5 indicators and 14 sub-indicators, which are then analyzed using Importance Performance Analysis (IPA) to measure service performance and toll road user satisfaction. The results of the analysis show that the value of the Customer Satisfaction Index (CSI) for the service quality of the Surabaya-Malang toll road as a whole is 82.09 (CSI Very Satisfied Category). The Surabaya-Malang toll road management service quality index (Expectation ratio value - MSI) as a whole is 3.28 (MSI is classified as Good), and is in line with the expectations of Surabaya-Malang toll road users (CSI Satisfaction is smaller than the CSI Average satisfaction average) includes (1) road conditions; (2) structure of emergency relief assistance; and (3) street lighting problems.